Optimizing Fabrication Outcome in Low-Cost FDM Machines. Part 2 - Tests - Buonamici, Francesco; Carfagni, Monica; Furferi, Rocco; Governi, Lapo; Saccardi, Marco; Volpe, Yary (Manufacturing Technology Journal, 2018)
Several models of FDM machines, characterized by different architecture and hardware components, have flooded the market in the last 5 years. As a result, given the high sensitivity of FDM to the specific machine characteristics, the search for optimal printing parameters is a renown problem. This two-parts paper proposes an easy-to-follow and low-cost procedure for the characterization of any given FDM machine. The method allows the evaluation of the effects of a wide selection of FDM process parameters on the quality of 3D printed parts. The first part focused on the definition of a series of metrics to be measured on a series of test prints to evaluate the quality of the produced parts. The evaluation of seven quality parameters on a single print is made possible thanks to: i) a specifically designed specimen that is made available to the user and ii) a rigorous and repeatable measurement procedure, which are both discussed in the first part of the paper. This second part presents the characterization procedure, the statistical tools used in the experimentation (DOE tools and principles are adopted throughout the experimentation) and provides guidelines to be used for the characterization of any FDM machine. The whole procedure is tested on a desktop FDM machine to demonstrate obtainable results, proving the efficacy of the proposed methodology and highlight strengths and drawbacks of the approach.
Keywords: Additive Manufacturing (AM); Fused Deposition Modeling (FDM); Process Optimization; Design of Experiments (DOE); 3D Printing